2005
DOI: 10.1002/jmv.20529
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early virological response to antiviral therapy by comparing four assays for HCV RNA quantitation using the international unit standard: Implications for clinical management of patients with chronic hepatitis C virus infection

Abstract: WHO International Standards for nucleic acid tests are used widely to compare the different assays used in HCV RNA quantitation. The aim of the study was to assess the impact of the international unit standard for measuring HCV RNA in the management of patients with chronic hepatitis C virus (HCV) infection. Twenty-seven naïve patients infected chronically by HCV were treated with ribavirin plus PEG-interferon-alfa-2b for 48 weeks. SVR was obtained for 16 patients (the other were non-responders). For HCV RNA q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…In a recent comparative study (11), we demonstrated that the absolute values obtained with these assays are different and that the HCV RNA viral load decline, assessed by different assays during antiviral therapy, can give different results regardless of the use of international units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent comparative study (11), we demonstrated that the absolute values obtained with these assays are different and that the HCV RNA viral load decline, assessed by different assays during antiviral therapy, can give different results regardless of the use of international units.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, false-positive and false-negative results, as well as variations in the HCV RNA level of Ͼ1 to 2 log IU, were observed. These results may have an impact on the management of patients receiving interferon therapy, for example, when treatment decisions are made using a single HCV RNA determination (11). Two standardized HCV RNA quantitative assays based on real-time PCR were recently developed (Abbott RealTime HCV and Roche Cobas TaqMan HCV).…”
mentioning
confidence: 99%
“…Third, while the introduction of an international standard has greatly improved the ability to compare results from different laboratories, there are still two problems. Studies have shown that even when assays are calibrated to the same international standard, results from different assays cannot be reliably compared (3,5,7). Finally, the international standard represents a single instance of a genotype 1 specimen.…”
Section: Figmentioning
confidence: 99%
“…I valori di HCV-RNA rilevati prima e durante il trattamento di combinazione con interferone pegilato e ribavirina costituiscono parametri indispensabili per indirizzare la decisione terapeutica, in particolare nei pazienti con infezione da genotipi 1, 4 e 6 (6,9,11). In questi soggetti livelli basali di viremia maggiori di 30.000 UI/mL ed una riduzione dei valori riscontarti dopo 12 settimane di trattamento inferiore a 2 log rispetto ai valori iniziali sono considerati predittivi di fallimento virologico e costituiscono una indicazione ad interrompere precocemente la terapia (13,24,26).…”
Section: Introduzioneunclassified